simplificar a expressão algébrica
![\frac{ {x}^{3} + 8}{x + 2} \frac{ {x}^{3} + 8}{x + 2}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Bx%7D%5E%7B3%7D+%2B+8%7D%7Bx+%2B+2%7D+)
Soluções para a tarefa
Respondido por
1
Resposta:
x² - 2x + 4
Explicação passo-a-passo:
x³ + 8 = x³ + 2³
= (x + 2)(x² - 2x + 4)
[(x + 2)(x² - 2x + 4)]/(x + 2) =
x² - 2x + 4
SombraNegrall:
vlw mano
Perguntas interessantes
Geografia,
10 meses atrás
Geografia,
10 meses atrás
Português,
10 meses atrás
Inglês,
1 ano atrás
Ed. Técnica,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás